Obscurity Of Norms: Nurses As Recipients Of Delegated Tasks From Anesthesiologists - Muhali Muhali; Carolina Kuntardjo (Fakultas Hukum Dehasen, 2024)
Nurses, who are an element of health human resources, also have an obligation to carry out their service duties professionally. Considering that nurses are legal subjects, in essence the relationship between nurses, patients and health facilities is a legal relationship. This research is normative legal research; by using types of secondary data obtained from various searches for journal articles, books and information through online news; related to the substance of the research. The aim of this research is to describe legal analysis using a statutory approach, a conceptual approach, and a historical approach to resolve the unclear norms of nurses as recipients of the abundant duties of an anesthetist. The results of this study confirm that understanding the laws and regulations, concepts and history of nurses as one of the health workers who receive various duties from anesthetists, brings changes to the view of the authority of nurses in anesthesia services.